Sea ice growth rates from tide‐driven visible banding. Issue 6 (8th June 2017) - Turner, Kate E.; Smith, Inga J.; Tison, Jean‐Louis; Verbeke, Véronique; McGuinness, Mark; Ingham, Malcolm; Vennell, Ross; Trodahl, Joe
Abstract: In this paper, periodic tide‐current‐driven banding in a sea‐ice core is demonstrated as a measure of the growth rate of first‐year sea ice at congelation‐ice depths. The study was performed on a core from the eastern McMurdo Sound, exploiting the well‐characterized tidal pattern at the site. It points the way to a technique for determining early‐season ice growth rates from late‐season cores, in areas where under ice currents are known to be tidally dominated and the ice is landfast, thus providing data for a time of year when thin ice prevents direct thickness (and therefore growth rate) measurements. The measured results were compared to the growth‐versus‐depth predicted by a thermodynamic model. Plain Language Summary: It is currently very difficult to measure sea‐ice growth rates, due to the danger of traveling on thin ice early in the growing season. This paper introduces the use of tidal patterns to determine sea‐ice growth rates at the end of the growing season, when ice cores can be taken. The technique utilizes the visible light and dark bands that are often present in sea ice near land, and are driven by changes in the tidal current beneath the ice. As well as being important for climate research, this method could contribute to the understanding biological ecosystems within the ice, by providing a method to date depths in an ice core where particular organisms are observed or samples taken. Key Points: Visible banding in congelation ice linked to periodic tidal currents Early season sea‐ice growth rates versus depth estimated directly from banding present in first‐year sea‐ice cores from McMurdo Sound Antarctica Growth rates related to total freezing time using simple ice growth model